Relevansi Manajemen Strategik Kepala Sekolah dalam Meningkatkan Mutu Pendidikan dan Daya Saing di Sekolah Dasar - Faizun Husni; Dwi Wahyudiati (Program Pascasarjana Universitas Pesantren Tinggi Darul Ulum (Unipdu) Jombang, 2022)
The quality of education determines the success and competitiveness of an educational institution. The quality of this education will not succeed without the right strategy in determining the overall quality of all components in education. The problems that occur in the world of education which include less effective learning, quality teachers, inadequate infrastructure, graduate competency standards, and programs that do not support the achievement of quality and competitiveness. One of the efforts to improve quality and competitiveness is through the application of strategic management, so as to be able to determine appropriate strategic steps to improve the quality of education and competitiveness. This study aims to reveal the conditions and analysis, implementation and evaluation of strategic management, and the results achieved from the implementation of strategic management in improving the quality of education and competitiveness in SD Islam Terpadu Aikmel. The research method used is descriptive-qualitative. Data collection techniques used are interviews, observations, and documentation studies. The results of this study are the relevance or linkage between strategic management and the quality of education and competitiveness, because the quality of education is related to everything that becomes the standard for achieving quality education both in terms of student achievement, quality of teachers, and school programs in general. This is because the quality of education is one of the benchmarks for the ability of schools to compete.